Upregulation of interferon-γ activation in patients with anti-interferon-γ autoantibodies immunodeficiency syndrome: insights from single-cell analysis - Liang, Si-qiao; Huang, Xue-mei; Liang, Xiao-na; Wu, Si-yao; Hong, Li-mei; Chen, Ni; Luo, Zeng-tao; Ning, Yan; Wang, Meng-chan; He, Zhi-yi (Frontiers in Immunology, 2026)
BackgroundAnti-interferon-γ autoantibodies (AIGAs) immunodeficiency syndrome is an emerging adult-onset immunodeficiency causing opportunistic infections. However, its comprehensive immune landscape remains elusive. This study presents the first single-cell RNA sequencing (scRNA-seq) analysis of AIGAs immunodeficiency syndrome, aiming to delineate its pathogenic mechanisms.MethodsWe performed scRNA-seq on peripheral blood mononuclear cells (PBMCs) from 8 AIGAs immunodeficiency syndrome patients (4 infective, 4 stable phase) and 3 healthy controls. Findings were validated by flow cytometry in an expanded cohort (15 patients vs. 10 controls).ResultsSingle-cell RNA sequencing of PBMCs from patients with AIGAs immunodeficiency syndrome identified a comprehensive immune subset profile, including effector memory CD4+ T cells, naive CD4+ T cells, regulatory T cells, GNLY+ CD8+ Tem, GZMK+ CD8+ Tem, naive CD8+ T cells, naive B cells, memory B cells, plasma cells, ISG+ atypical B cells, monocytes, and NKT cells. ScRNA-seq analysis revealed a significantly higher proportion of Th1 cells (16.62% vs. 6.94% in controls) and ISG+ B cells (2.95% vs. 0.53%), alongside a lower proportion of plasma cells (9.30% vs. 17.79%) and memory B cells (9.54% vs. 27.35%). Flow cytometry consistently confirmed the increase in Th1 cells (21.84% [14.87–27.57] vs. 11.96% [7.19–15.74]) and decreases in marginal zone B cells (2.87% [1.71–4.45] vs. 8.60% [6.77–15.65]), memory B cells (13.85% [5.72–20.23] vs. 22.96% [16.39–33.83]), and class-switched B cells (6.11% [2.39–9.10] vs. 10.18% [5.35–15.77]). Transcriptome analysis demonstrated upregulated expression of interferon-response and HLA genes (e.g., HLA-DQB1, HLA-DQA1, HLA-DRB1), whereas IRF1 was downregulated across all subsets; functional enrichment analyses further highlighted significant activation in IFN signaling and B cell activation pathways. CellChat and pseudotime analyses indicated that CD4+ Tem and CD14+ monocytes drive sustained Th1 inflammation and monocyte hyperactivation through enhanced pro-inflammatory and antigen-presenting interactions, with T-cell differentiation skewed toward terminal effectors and B-cell development disrupted by ISG+ B cell emergence, premature plasma cell formation, and IGLC3-biased class switching, collectively delineating the interferon-mediated immunopathology of AIGAs immunodeficiency syndrome.ConclusionsIn summary, this first single-cell atlas maps AIGAs immunodeficiency syndrome as a Th1-skewed, IFN-γ-driven disorder sustained by CD4+ Tem–CD14+ monocyte crosstalk. It combines T-cell activation, expanded Th1 and ISG+ B cells, and loss of memory/plasma B cells to drive autoantibody generation. Skewed T- and B-cell trajectories and polygenic up-regulation of interferon/HLA genes provide a clear mechanistic rationale for targeted therapy.